Revisión Bibliográfica: Aplicación De Igy En La Medicina Porcina (2022)
Immunoglobulin Y (IgY) is a class of antibodies of major importance in birds, reptiles, amphibians, and lungfish, which play a similar role to mammalian IgG. Egg yolk has been shown to be a convenient source of polyclonal antibodies. That it has been used because it is an inexpensive and effective source of antibodies and because it is a therapy that reduces bleeding in laboratory animals and is minimally invasive. The production of IgY antibodies is influenced by a series of factors such as the type of antigen to be used, the dose, the adjuvant used, the route of application, the frequency of inoculation, the age and the stage of development. In birds, it is a technique that has been used with a wide variety of antigens. Likewise, the route that has been most used for the production of IgY in chickens is the intramuscular route, in which the inoculation is usually in the muscle. of the breast, is a therapy that has been used more and more due to its great advantages.